PERAN PUBLIC RELATIONS DALAM MENINGKATKAN BRAND IMAGE PADA BENING’S CLINIC CABANG KEMANG JAKARTA SELATAN - Fitria, Putri; Razali, Geofakta (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Improving brand image is an important aspect of business in the field of beauty clinics. Likewise for Bening’s Clinic Kemang South Jakarta Branch, improving a good brand image by public relations to customers so as to increase satisfaction and have a good effect on service. This is the background so that the role of public relations can improve brand image. The purpose of this study was to analyze the role of Public Relations in enhancing the brand image of Bening Clinic, Kemang Branch, South Jakarta through Instagram as a service company providing facial skin health services in Indonesia. In addition, this study aims to analyze the obstacles and solutions implemented to overcome obstacles to the role of Public Relations in increasing the brand image of the Bening Clinic, Kemang Branch, South Jakarta. This research method uses a qualitative descriptive method. This study uses Dozier and Broom’s concept regarding the role of Public Relations and Atmoko’s concept regarding Instagram features and Biel’s concept regarding brand image dimensions. Data collection techniques using in-depth interviews, observation, and documentation. The results of this study indicate that the role of Public Relations at Bening’s Clinic, Kemang Branch, South Jakarta, uses Instagram to find out the experiences felt by customers, both positive and negative experiences. Instagram content from Bening’s Clinic Public Relations, Kemang South Jakarta Branch is very interesting, informative, and has a huge impact on customers because the information conveyed is quite routine through the Brand Ambassador by utilizing the features available on Instagram as an intermediary medium in enhancing brand image.